Oxidation of 2,4.6-Trinitroresorcine Using Zero-Valent Iron - Quoc Trung, Le; Duc Hung, Nguyen; Hoai Nam, Nguyen; Van Chung, Tran; Francis Cheng, I. (Asian Journal of Chemistry, 2010)
This paper describes the character of the reduction of 2,4.6-trinitroresorcine (TNR) by zerovalent iron (ZVI) in anaerobic conditions and the oxidative reaction of amine resorcine in the system of ZVI-EDTA-O2. The products of TNR by ZVI in anaerobic conditions were amine resorcine compounds. These compounds tend to be easier to be oxidized by the free radical OH• generated in the system of ZVI-EDTA-O2. HPLC method and COD analysis have been used for monitoring efficiency of reactions. The experiments suggested that the removal of TNR from groundwater is likely implemented by two steps. The first step is reduction of TNR by ZVI to form amine resorcine. The second step is oxidation of amine resorcine in system consisting of ZVI-EDTA-O2. From the obtained results a model for TNR contaminated groundwater treatment has been suggested.